(untitled) (Journal of Universal Science Research, 2023)
This research explores cellulose extraction processes suitable for obtaining low-quantity products from the stem part of the local Saflor plant. Saflor stem cellulose is considered a promising source for sustainable and biodegradable materials. The study optimizes cellulose extraction methods, characterizes the obtained cellulose, and evaluates its suitability for low-quantity product development. This research contributes to the sustainable utilization of local resources and the production of environmentally friendly materials.